Morphological and Biochemical Responses Associated With Resistance to Earias Vittella Fab. (Lepidoptera: Noctuidae) In Okra Varieties (Bangladesh Journal of Botany, 2021)
Response of morphological and biochemical traits against okra shoot and fruit borer in different okra varieties were studied. Among the fifteen okra varieties under test Kashi Satdhari was the most superior variety as it showed lowest (2.60) per cent shoot damage followed by D-1-87-5 (3.62%) and Pusa A-4 (4.24%). On the contrary, in Pusa Sawani highest level of shoot infestation (16.23%) followed by SB-2 (13.74%) as against Kashi Pragati (check) 10.08 per cent were recorded. Further, okra variety Kashi Satdhari (7.87%) showed lowest fruit infestation and was considered as least susceptible variety which was at par with NO-136 (8.77%), D-1-87-5 (9.12%) and Kashi Leela (9.38%). Amongst all the okra varieties evaluated for their susceptibility to fruit infestation, Pusa Sawani and VRO-03 showed relatively higher fruit infestation i.e. 35.17 and 33.41 per cent, respectively and registered as the most inferior varieties against (26.12%) Kashi Pragati (check). The correlation study between fruit infestation and morphological factors implied that primary branching and trichome length adversely affect the borer infestation. Further, phenol and phosphorus availability in host plant also showed negative effect on shoot and fruit borer infestation.Bangladesh J. Bot. 50(4): 1059-1066, 2021 (December)